CHARACTERIZATION OF COMPOSITE CONTAINING LDPE (LOW DENSITY POLY ETHYLENE) AND MODIFIED PINEAPPLE LEAF FIBER - Lestari Wardani; Noerati Noerati; Doni Sugiyana (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2020)
CHARACTERIZATION OF COMPOSITE CONTAINING LDPE ( LOW DENSITY POLY ETHYLENE) AND MODIFIED PINEAPPLE LEAF FIBER. Pineapple leaf fiber could be used as a reinforcing material in natural fiber composites production with a synthetic polymer matrix. The typical problem in this process was the weak bond between the fiber component and the matrix. This study aimed to improve the bonds strength between pineapple leaf fibers and the polymer matrix of LDPE (Low Density Poly Ethylene) by modifying pineapple leaf fibers. The modification of pineapple leaf fibers was carried out through an enzymatic process using the xylanase enzyme. A modified fiber was then used as a fiber component in the composite using a commercial LDPE plastic matrix. Composites were made by the sandwich method using a hotpress machine at a temperature of 130 °C for 10 minutes. The evaluation of the composites were carried out by testing the tensile strength properties using the Tensolab tool and thermal properties using the TGA (Thermal Gravimetry Analysis) instrument. The results of the mechanical properties test of the composite showed the modified pineapple leaf fiber-based composite had a better tensile strength (34.3 MPa) than the untreated pineapple leaf fiber-based composite (30.2 MPa). The results of the thermal properties test showed the decreasing of the mass occurred at temperature of 300-350 °C due to degradation of the fiber,and it completely degraded at temperature of 450 °C.